Novel insights in rehabilitation of neglect, 2nd Edition - Tanja Nijboer (Frontiers Research Topics, 2015)
Hemispatial neglect is the failure to report, respond to, or orient to novel or meaningful stimuli presented in the contralesional visual field. It constitutes one of the most invalidating neurological disorders that can occur after stroke. It is therefore important to treat neglect as adequate as possible and much of the research dedicated to neglect therefore focuses on rehabilitation. In this special topic, you will find 29 articles on the rehabilitation of neglect. This Research Topic has opened new perspectives, and has given us an indication of where the field is going. Although some of the current rehabilitation techniques have proven to be beneficial, there is limited agreement on the most valuable technique or the mechanisms underlying the ameliorating effects.